Asymmetric Ruthenium‐Catalyzed Hydrogenation of 2‐ and 2, 9‐Substituted 1, 10‐Phenanthrolines1. Issue 28 (5th June 2013) - Wang, Tianli; Chen, Fei; Qin, Jie; He, Yan‐Mei; Fan, Qing‐Hua
<x xml:space="preserve">Abstract</x> A 'Phen'atic: The title reaction proceeds in the presence of the chiral cationic ruthenium diamine catalyst (R, R)‐1 (Tf=trifluoromethanesulfonyl, Ts=4‐toluenesulfonyl). Both chiral 1, 2, 3, 4‐tetrahydro‐ and 1, 2, 3, 4, 7, 8, 9, 10‐octahydro‐1, 10‐ phenanthroline derivatives could be obtained in high yields with excellent enantio‐ and diastereoselectivity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>